Kecurangan, BUMN Fraud Pentagon: Deteksi Kecurangan Laporan Keuangan Pada Badan Usaha Milik Negara - Nurhakim, Agus Lukman; Harto, Puji (E-Jurnal Akuntansi; Vol 33 No 2 (2023)DO - 10.24843/EJA.2023.v33.i02.p03, 2023)
Fraudulent financial statements, especially in State-Owned Enterprises (BUMN) companies, is a criminal act of corruption with a very large level of financial losses. The research aims to test the pentagon fraud theory in detecting fraudulent financial statements in state-owned companies. The research sample is 20 state-owned companies from 2018-2021 which are listed on the IDX. This study took samples of SOEs with various industrial segments, besides that this study used a measure of government ownership as a proxy for rationalization, this proxy is still very rarely used. Data analysis in this study used logit regression analysis. The research results show that only financial stability and replacement of directors have a significant effect on the possibility of fraudulent financial statements, while other variables in the Fraud Pentagon have no effect. Keywords: Fraud Pentagon; Fraudulent Financial Statement; Soes